Chest X-ray features of SARS-CoV-2 in the emergency department: a multicenter experience from northern Italian hospitals. (August 2020) - Ippolito, Davide; Maino, Cesare; Pecorelli, Anna; Allegranza, Pietro; Cangiotti, Cecilia; Capodaglio, Carlo; Mariani, Ilaria; Giandola, Teresa; Gandola, Davide; Bianco, Ilaria; Ragusi, Maria; Franzesi, Cammillo Talei; et al.
Abstract: Objectives: To evaluate the imaging features of routine admission chest X-ray in patients referred for novel Coronavirus 2019 infection. Methods: All patients referred to the emergency departments, RT-PCR positive for SARS-CoV-2 infection were evaluated. Demographic and clinical data were recorded. Two radiologists (8 and 15 years of experience) reviewed all the X-ray images and evaluated the following findings: interstitial opacities, alveolar opacities (AO), AO associated with consolidation, consolidation and/or pleural effusion. We stratified patients in groups according to the time interval between symptoms onset (cut-off 5 days) and X-ray imaging and according to age (cut-off 60 years old). Computed tomography was performed in case of a discrepancy between clinical symptoms, laboratory and X-ray findings, and/or suspicion of complications. Results: A total of 468 patients were tested positive for SARS-CoV-2. Lung lesions primarily manifested as interstitial opacities (71.7%) and AO opacities (60.5%), more frequently bilateral (64.5%) and with a peripheral predominance (62.5%). Patients admitted to the emergency radiology department after 5 days from symptoms onset, more frequently had interstitial and AO opacities, in comparison to those admitted within 5 days, and lung lesions were more frequently bilateral and peripheral. Older patients more frequently presented interstitial and AO opacities in comparison to younger ones. Sixty-eight patients underwent CT that principally showed the presence of ground-glass opacities and consolidations. Conclusions: The most common X-ray pattern is multifocal and peripheral, associated with interstitial and alveolar opacities. Chest X-ray, compared to CT, can be considered a reliable diagnostic tool, especially in the Emergency setting. Highlights: SARS-CoV-2 pulmonary findings are typically bilateral and subpleural. Symptoms onset time of 5 days is a reliable cut-off. Pulmonary findings are age-related.